2018
DOI: 10.1097/ajp.0000000000000564
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of a Recent History of Disabling Low Back Pain in Community-dwelling Older Persons

Abstract: Our study supports the link between disabling LBP and other age-related chronic conditions in a middle-income country with a rapidly aging population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
25
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 66 publications
1
25
0
1
Order By: Relevance
“…An approach regarding complaints of LBP at different moments was found in this systematic review. Eight studies (18-25) addressed acute LBP prevalence, and 21 studies (26-46) addressed chronic LBP prevalence; however, six studies (47-52) did not specify the prevalence period investigated.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…An approach regarding complaints of LBP at different moments was found in this systematic review. Eight studies (18-25) addressed acute LBP prevalence, and 21 studies (26-46) addressed chronic LBP prevalence; however, six studies (47-52) did not specify the prevalence period investigated.…”
Section: Resultsmentioning
confidence: 99%
“…Functional disability due to LBP was investigated in 60% of the studies, and LBP was shown to hinder functionality (18,20,21,23,27,28,30,37,39) and result in major dependence for daily living activities (24,29,48,38,52) and physical capacity (30,33,36,24,46).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dutch longitudinal data from the Doetinchem Cohort Study, obtained from four self-reported pain measurements taken every five years with a sample of 3485 adults, aged 25-71 to 40-86 years concluded that individuals with shorter sleep period, smoking, obesity, and poor perception of mental health are more prone to pain 38 . Accordingly, the PAINEL Study, derived from the FIBRA Network Study, conducted in the city of Belo Horizonte, with 378 participants over 60 years, among the findings, found that individuals with disabling low back pain were more likely to have shorter sleep time 39 . In general, the manifestation of response to the pain of individuals may cause changes in sleep pattern and other physio-pathological processes, considering an association between pain and adequate sleep 14,27 .…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] Pain has a profound negative impact on patients' and caregivers' lives. Unrelieved pain results in psychological suffering (depression) 7 and poor quality of life for patients. 8,9 A priority of hospice care and palliative care is to provide effective pain management for patients.…”
mentioning
confidence: 99%